The 1563 Ruthenian Translation of the Czech Lucidář in a Manuscript Copy of the First Half of the 17th Century: Publication - Temčinas, Sergejus (Slavistica Vilnensis, 2021)
The younger manuscript copy of the 1563 Ruthenian translation of the Czech Lucidář is published in full (Moscow, State Public Historical Library of Russia, Department of Rare Books, Ms. 11, fol. 67v–89), which has preserved the afterword with the translation date and fills in a significant gap (twenty questions and answers) of the earlier manuscript copy.